EKSPLORASI DAN EKSPLOITASI PERTAMBANGAN MINYAK DAN GAS BUMI DI LAUT NATUNA BAGIAN UTARA LAUT YURIDIKSI NASIONAL UNTUK MENINGKATKAN KESEJAHTERAAN MASYARAKAT DI KEPULAUAN NATUNA - Annisa Purwatiningsih; Masykur . (REFORMASI, 2012)
Comprehensive understanding of the issue of fuel oil (BBM) and pay attention to the characteristics of oil and gas are vital and strategic, limited capital, and open global trading system (free competition) could affect the domestic economy and the Natuna Islands region as a frontier area. This will open up new horizons and the mindset of the problems occurred. In this paper, the authors attempt to provide an objective picture of the increase in mining exploration and exploitation of oil and gas in Natuna Islands as oil and gas producer, has the largest natural gas reserves in the Asia Pacific region and even the world's largest and exploration of alternative energy as a strategic goal of security the long-term energy strengthen strategic reserves of oil and gas, and to avoid an energy crisis. Oil contents in the Natuna Sea made foreign investors who invest in the Natuna have impact on the regional economy in Natuna. With the utilization of oil and gas exploration can be sensed benefits (direct benefit) by the the communities around the activities of depletion oil and gas resource and improve the life of the Natuna Islands.